2015
DOI: 10.1021/es505434r
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of PAH and Nitro-PAH Emissions from Nonroad Diesel Engines

Abstract: More stringent emission requirements for nonroad diesel engines introduced with U.S. Tier 4 Final and Euro Stage IV and V regulations have spurred the development of exhaust aftertreatment technologies. In this study, several aftertreatment configurations consisting of diesel oxidation catalysts (DOC), diesel particulate filters (DPF), Cu zeolite-, and vanadium-based selective catalytic reduction (SCR) catalysts, and ammonia oxidation (AMOX) catalysts are evaluated using both Nonroad Transient (NRTC) and Stead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 32 publications
4
19
0
Order By: Relevance
“…7). The average ratios of the PAHs in excavator exhaust obtained in this study are similar to those reported by Liu et al (2015). The E4 excavator showed obvious differences in the ratios of BaA / (BaA +vChry), IcdP / (IcdP + BghiP), and Flua / (Flua + Pry) from those for the other excavators.…”
Section: Particulate Matter Composition For Individual Excavatorsupporting
confidence: 87%
“…7). The average ratios of the PAHs in excavator exhaust obtained in this study are similar to those reported by Liu et al (2015). The E4 excavator showed obvious differences in the ratios of BaA / (BaA +vChry), IcdP / (IcdP + BghiP), and Flua / (Flua + Pry) from those for the other excavators.…”
Section: Particulate Matter Composition For Individual Excavatorsupporting
confidence: 87%
“…The formation mechanism of Nitro-PAHs through the nitration reaction during the combustion process in the cylinder has been investigated by several researches. Nevertheless, the knowledge about this process remains inconclusive (Kielhorn et al, 2003;Heeb et al, 2008;Liu et al, 2015). During the combustion, Nitro-PAHs can be formed by electrophilic substitution reactions in the presence of NO x and the combination of high temperatures.…”
Section: Particle-phase Nitro-pahsmentioning
confidence: 99%
“…In a recent study, Liu et al (2015) examined the emission of Nitro-PAHs using various types of aftertreatment systems in different configurations. When testing DOC + SCR, the emissions of PAHs increased compared to the results of the engine without any after-treatment system.…”
Section: Particle-phase Nitro-pahsmentioning
confidence: 99%
See 2 more Smart Citations